#### Answer

$\color{blue}{\left\{−10,10\right\}}$

#### Work Step by Step

The given expression is equivalent to:
$t^2−10^2=0$
Factor the binomial using the formula $a^2−b^2=(a−b)(a+b)$ with $a=t$ and $b=10$ to obtain:
$(t−10)(t+10)=0$
RECALL:
The zero factor theorem states that if $a\cdot b=0$, then either $a=0$ or $b=0$ or both are zero.
Equate each factor to zero, then solve for $t$:
$t−10=0
\\t−10+10=0+10
\\t=10$
or
$t+10=0
\\t+10−10=0−10
\\t=−10$
Thus, the solution set is $\color{blue}{\left\{−10,10\right\}}$.